2006
DOI: 10.1309/c7je8bvl8420v5vt
|View full text |Cite
|
Sign up to set email alerts
|

Sessile Serrated Adenomas With Low- and High-Grade Dysplasia and Early Carcinomas

Abstract: Sessile serrated adenomas (SSAs) show serrations typical of hyperplastic polyps but display architectural differences and lack traditional dysplasia. SSAs with foci of low- (LGD) or high-grade dysplasia (HGD) or early invasive carcinoma are seldom biopsied and, thus, are not well studied. Immunohistochemical analysis for MLH1, MSH2, MSH6, and PMS2 (mismatch repair gene products) was performed on colon biopsy specimens from 11 patients (age range, 54-87 years; 4 men and 7 women) showing SSA with LGD (n = 1), HG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(39 citation statements)
references
References 23 publications
2
36
0
1
Order By: Relevance
“…1 Hypermethylation of MLH1 has been shown to coincide with the development of both dysplasia and dMMR with MSI in SSA/P. 17 In addition to near uniform BRAF mutations in SSA/P-associated cancers, we found loss of MLH1 in 79% of tumors in this cohort suggesting that SSA/Ps are precursor lesions primarily for sporadic dMMR/MSI colon cancers.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…1 Hypermethylation of MLH1 has been shown to coincide with the development of both dysplasia and dMMR with MSI in SSA/P. 17 In addition to near uniform BRAF mutations in SSA/P-associated cancers, we found loss of MLH1 in 79% of tumors in this cohort suggesting that SSA/Ps are precursor lesions primarily for sporadic dMMR/MSI colon cancers.…”
Section: Discussionmentioning
confidence: 59%
“…20 This finding suggests that epigenetic silencing of MLH1 may be the critical step for SSA/P to progress to dysplasia and subsequent cancer. 17 . We acknowledge that our series of cancer-associated SSA/Ps represent a highly selected subset for which additional research is needed to identify factors associated with cancer predisposition.…”
Section: Discussionmentioning
confidence: 99%
“…Those SSADs with intact MLH1 and low p53 expression may represent either a stable mixed polyp or an SSA with de novo low-grade dysplasia, whereas SSADs with loss of MLH1 and high p53 expression usually show high-grade dysplasia and probably represent a transformation phase between SSAs and microsatellite instability (MSI) type colonic adenocarcinoma. Other studies have also demonstrated progression from SSAs to MSI-type colonic adenocarcinoma in SSADs with loss of MLH1 [23,24]. This also suggests that some TSAs arise de novo and not from SSAs, and that dysplasia developing within SSAs may represent a different pathway.…”
Section: Discussionmentioning
confidence: 86%
“…García-Solano, et al . postulated that precursor sessile serrated adenoma frequency is probably underestimated, because sessile serrated adenomas can undergo complete histological dysplasia and high-grade transformation, leading to a traditional serrated adenoma or in situ adenocarcinoma appearance [18, 27]. …”
Section: Discussionmentioning
confidence: 99%